Political Polarization along the Rural-Urban Continuum? The Geography of the Presidential Vote, 2000–2016. Issue 1 (July 2017) - Scala, Dante J.; Johnson, Kenneth M.
This article documents the diversity of political attitudes and voting patterns along the urban-rural continuum of the United States. We find that America's rural and urban interface, in terms of political attitudes and voting patterns, is just beyond the outer edges of large urban areas and through the suburban counties of smaller metropolitan areas. Both Barack Obama and Hillary Clinton performed well in densely populated areas on the urban side of the interface, but they faced increasingly difficult political climates and sharply diminished voter support on the rural side of the interface. The reduction in support for Clinton in 2016 in rural areas was particularly pronounced. Even after controlling for demographic, social, and economic factors (including geographic region, education, income, age, race, and religious affiliation) in a spatial regression, we find that a county's position in the urban-rural continuum remained statistically significant in the estimation of voting patterns in presidential elections.